Contribution of ULF Wave Activity to the Global Recovery of the Outer Radiation Belt During the Passage of a High‐Speed Solar Wind Stream Observed in September 2014. Issue 3 (18th March 2019) - Da Silva, L. A.; Sibeck, D.; Alves, L. R.; Souza, V. M.; Jauer, P. R.; Claudepierre, S. G.; Marchezi, J. P.; Agapitov, O.; Medeiros, C.; Vieira, L. E. A.; Wang, C.; Jiankui, S.; et al.
Abstract: Energy coupling between the solar wind and the Earth's magnetosphere can affect the electron population in the outer radiation belt. However, the precise role of different internal and external mechanisms that leads to changes of the relativistic electron population is not entirely known. This paper describes how ultralow frequency (ULF) wave activity during the passage of Alfvénic solar wind streams contributes to the global recovery of the relativistic electron population in the outer radiation belt. To investigate the contribution of the ULF waves, we searched the Van Allen Probes data for a period in which we can clearly distinguish the enhancement of electron fluxes from the background. We found that the global recovery that started on 22 September 2014, which coincides with the corotating interaction region preceding a high‐speed stream and the occurrence of persistent substorm activity, provides an excellent scenario to explore the contribution of ULF waves. To support our analyses, we employed ground‐ and space‐based observational data and global magnetohydrodynamic simulations and calculated the ULF wave radial diffusion coefficients employing an empirical model. Observations show a gradual increase of electron fluxes in the outer radiation belt and a concomitant enhancement of ULF activity that spreads from higher to lower L‐shells. Magnetohydrodynamic simulation results agree with observed ULF wave activity in the magnetotail, which leads to both fast and Alfvén modes in the magnetospheric nightside sector. The observations agree with the empirical model and are confirmed by phase space density calculations for this global recovery period. Key Points: ULF waves reached the lowest magnetospheric L‐shells at the end of the period on 24 September Relativistic electron population reached the lowest magnetospheric L‐shells at the end of the period on 24 September Enhancement of the electron flux occurs concomitantly with the Alfvénic fluctuations following a solar wind sector boundary crossing